Development of aluminium-copper die-attach alloy for high operational temperature application / Siah Meng Zhe - Siah, Meng Zhe (2019)
Die attach material plays an important role in electronic packaging as it serves as an interconnection between SiC device and substrate, provides physical and mechanical support and serves as a heat dissipating path. An aluminum-copper (Al-Cu) nanopaste formulated by mixing Al and Cu nanoparticles with organic additives (i.e., resin binder, terpineol and ethylene glycol) which is meant for high-temperature die-attach applications has been developed. Various weight percent of V006A (4%,5%,6% and 7%) and the Al loading (10%, 20%, 30% and 40%) have been loaded into the Al-Cu nanopaste, followed by sintering in open air at temperature of 380°C for 30 min without the need of applied external pressure. The physical and electrical properties were investigated. X-ray diffraction results showed that Al2Cu and CuO phases were formed in sintered Al-Cu nanopaste. Overall, Al-Cu nanopaste with 5% V006A has exhibited the best electrical conductivity [21??.cm], lowest oxygen element [15.36%] and smallest crystallite size [8.15nm], which is suitable for high temperature electronic applications. Also, Al0.5-Cu4.5 demonstrated the lowest electrical resistivity at 21.70 ??.cm, which is acceptable for a high temperature die-attach material.